The Role of Training in Muscle Fiber Type Composition Changes Among Petanque Athletes in Soppeng - Siti Nurhalizah Mutia Aulria; Riswan Asmari (Universitas Pejuang Republik Indonesia, 2026)
Background: Petanque is a precision sport requiring fine motor neuromuscular control, postural stability, and limb strength-endurance. Despite growing popularity in Soppeng Regency, South Sulawesi, scientific evidence on structured training effects on muscle fiber composition in petanque athletes remains scarce. Objectives: This study analyzed muscle fiber type composition changes among 36 Soppeng petanque athletes (18 male, 18 female) following a 12-week periodized training program, comparing adaptations across competition categories (buts, tir, mele). Methods: A quasi-experimental pre-test/post-test design was applied to three groups (n=12 each). Measures included handgrip dynamometry, one-leg stance, isokinetic wrist strength, shoulder endurance, 30-meter sprint, VO₂max, and ultrasound CSA of m. flexor digitorum superficialis and m. deltoid. Results: All groups showed significant improvements (p<0.05). Buts athletes demonstrated superior gains in handgrip (+18.4%), balance (+42.3%), and wrist endurance (+31.2%), reflecting Type I fiber dominance. Tir athletes showed greater shoulder explosive power (+24.6%) and sprint improvement (-6.8%), indicating Type II hypertrophy. Mele athletes exhibited balanced adaptations. Conclusions: Petanque-specific training produces category-dependent muscle fiber adaptations, providing the first empirical evidence base for petanque muscle physiology in Soppeng.